Adolf Januszkiewicz jako pośrednik oraz spoiwo łączące kulturę kazachską i europejską - Kenżalin, Żumabiek (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
The paper is devoted to the role played by Adolf Januszkiewicz, a poet and insurgent in the November uprising, in Polish-Kazakh relations. A graduate of Vilnius University, Januszkiewicz was among eminent Polish activists sent by the Tsar into exile in Siberia and Kazakhstan. Over twenty years spent in close contact with the inhabitants ofthe Great Steppe shaped Januszkiewicz’s peculiar attitude to the Kazakh nation. His journals and letters have been translated into several European languages. They still remain an interesting source of knowledge about the culture and customs of Kazakhs then. They are highly appreciated in Kazakhstan as an example of the thorough approach taken by an educated representative of a progressive European culture towards the life of a nomadic people. The positive image of Poles generated by the 19th century exiles has laid the foundations for the friendly attitude the Kazakh have had towards successive groups of Poles who found themselves in their country. At present, the sizeable Polish minority is well integrated with Kazakh society. The legacy of such activists as Adolf Januszkiewicz provides excellent foundations for the advancement of Polish-Kazakh relations.
Adolf Januszkiewicz as an intermediary and link between Kazakh and European culture